Life on the edge : [videorecording (DVD)] : a guide to Pacific coastal habitats - Currie, Nancy; Sefton, Nancy (Seattle Aquarium, 2004)
Explores Pacific coastal habitats of sandy beaches, eelgrass beds, rocky shores, estuaries and kelp forests from Alaska to California. Discusses coastal geology, tides, intertidal zonation, key elements of each habitat, and their residents. DVD includes a phyla review of Pacific Coastal marine animals. Presented in seven chapters with a printable teacher's guide.